Optimal Monetary Policy in a Currency Union: Implications of Country-specific Financial Frictions - Jochen Michaelis; Jakob Palek (Credit and Capital Markets – Kredit und Kapital, 2016)
There is growing empirical evidence that the strength of financial frictions differs across countries. Using the cost channel approach, we show how the introduction of (country-specific) financial frictions alters the optimal monetary responses to union-wide and national non-financial shocks in a New Keynesian model of a two-country monetary union. By causing a cost-push effect on inflation, financial frictions make monetary policy less effective in combating inflation. We show that the optimal response to the decline in effectiveness is a stronger use of the interest-rate instrument. On the other hand, the larger the differential of financial frictions across member states, the less aggressive will the optimal monetary policy be. For almost all parameter constellations, our welfare analysis suggests a clear-cut ranking of policy regimes: commitment outperforms the Taylor rule, the Taylor rule outperforms strict inflation targeting, and strict inflation targeting outperforms discretion. – – Optimale Geldpolitik in einer Währungsunion: Implikationen länderspezifischer Finanzmarktfriktionen Wachsende empirische Evidenz deutet auf eine von Land zu Land divergierende Ausprägung von Finanzmarktfriktionen hin. Wir integrieren länderspezifische Finanzmarktfriktionen in ein Neukeynesianisches Zwei-Länder-Modell einer Währungsunion und untersuchen in diesem Rahmen die Frage, wie die optimale Geldpolitik auszugestalten ist angesichts von unionsweiten und nationalen nicht- finanziellen Schocks. Aufgrund der direkten Wirkung auf die Grenzkosten der Unternehmen mindern Finanzmarktfriktionen die Effizienz der Geldpolitik in der Steuerung der Inflation. Wir zeigen, dass es optimal ist auf die verringerte Effizienz mit einer stärkeren Nutzung des Zinsinstruments zu reagieren. Andererseits gilt: Je größer die Differenz in den länderspezifischen Finanzmarktfriktionen, desto weniger aggressiv ist die unionsweite Geldpolitik. Die Wohlfahrtsanalyse offenbart für fast alle möglichen Parameterkonstellationen ein eindeutiges Ranking hinsichtlich der Politikregime: Commitment übertrifft die Taylor Regel, die Taylor Regel übertrifft Strict Inflation Targeting, und Strict Inflation Targeting übertrifft Discretion.
Keywords: E31; E52; F41; 330; financial frictions; cost channel; optimal monetary policy; monetary union